Pengaruh Lama Waktu Penurunan Kadar Air terhadap Kualitas Fisikokimia Madu Kapuk dan Madu Rambutan - A. Apriantini; Y. C. Endrawati; Z. Astarini (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
Honey is a livestock product that has high nutritional content and beneficial for the health of human body, but Improper post-harvest handling can cause short shelf life. The aim of this study was to analyze the physicochemical quality of kapok honey and rambutan honey after moisture reduction treatment using a dehumidifier. The kapok and rambutan honey samples had three different duration of moisture reduction treatments, included 0 hours, 4 hours, and 8 hours at room temperature ±30 °C. Each treatment level was repeated four times. This study used descriptive analysis. The physicochemical analysis during the treatment consists of water content, pH, ash content, viscosity, color, and sugar content. The results showed that the treatment of honey for 8 hours at a temperature of ±30 °C had a water content that was close to the SNI standard. Moreover, the nutritional content of honey in the 8-hour treatment of moisture reduction had the best results in the physicochemical quality both of kapok honey and rambutan honey even though the treatment did not affect the ash content of rambutan honey and the pH value of the two types of honey. The moisture reduction did not reduce the physicochemical quality in 2 types of honey.